The Utilization of Artificial Intelligence in Islamic Religious Education Learning in the Hiper Digital Era in Islamic High School - Putra, Ahmad Fakk Dominika Taqi Aha; Marno, Marno; Esha, Muhammad In’am; Haris, Abd.; Ahaputra, MA. Sadra (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study aims to analyze the use of artificial intelligence in Islamic Religious Education learning in the hyper-digital era in Islamic High School. The study focuses on the forms of AI utilization, the opportunities it offers, the challenges it presents, and its implications for pedagogical practices in Islamic education. This research employed a qualitative approach with a field research design and descriptive-analytical method. Data were collected through observation, semi-structured interviews, and documentation, and were analyzed using an interactive model consisting of data collection, data condensation, data display, and conclusion drawing. The findings reveal that the use of AI in Islamic Religious Education learning in Islamic High School remains at an early stage and has not yet been systematically integrated into lesson planning, implementation, or evaluation. Nevertheless, AI has the potential to support learning that is more interactive, adaptive, and relevant to students’ characteristics in the digital era. On the other hand, this study also identifies several challenges, including the lack of clear pedagogical integration, the risk of educational dehumanization, the potential bias and inaccuracy of religious information, issues of scholarly authority, and the possible misuse of technology. Therefore, the use of AI in Islamic Religious Education learning should be positioned as a supporting tool that is managed selectively, critically, and value-based in order to remain aligned with the goals of Islamic education.